The mediating effect of work engagement between its antecedents and outcome among academics in research and development at Malaysian public universities - Tauhed, Siti Zainab; Mohd Rasdi, Roziah; Abu Samah, Bahaman; Ibrahim, Rahinah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Work engagement (WE) among employees is important to achieve both individual and organizational goals. Most organizations value engaged employees as they are able to promote job performance and manage their career. Failure to make employees engaged would result in disengagement where they are less interested in their tasks, always feel tired and passive, and only wait for time to go home. Work context influences the type of antecedents for work engagement. Thus, this paper aims to determine the antecedents of WE that serve as the motivational drivers for academics to be engaged in Research and Development (R&D). In addition, most of the studies on work engagement have extended their research to investigate the outcome of work engagement. Accordingly, this paper will also examine WE’s outcome. In such case, work engagement is placed as mediator that facilitate the relationship between its antecedents and outcome. Using previous empirical studies and related theories on work engagement, this paper discusses academics’ work engagement in R&D and its outcome. This paper also recommends the antecedents for academics work engagement in R&D and its outcome. Potential antecedents such as organizational factors, individual factors and job resources have been associated with employee’s inclination to engage in their job. Career success is the possible outcome at the individual level influenced by WE. This paper focuses on developing a conceptual framework about work engagement-career success for academics especially in R&D at Malaysian Public Universities. Establishing this new knowledge is instrumental in identifying factors, re-evaluating existing practices, outlining efficient strategies and interventions to make employees engaged in their job. An engaged employees would be immersed in performing their job, and thus lead to their individual career success. This paper supports theory of work engagement in R&D, specifically referring to elements of organizational factors, individual factors and job resources which enhancing academics’ engagement in R&D and career success at public universities. Finally, this paper proposing that these elements to be considered in future theoretical framework development on academics work engagement in R&D and their career success.